A geografia do clima em Copacabana - Malheiros, Tatiana dos Santos (2010)
Climate geography in Copacabana reflects and raises the necessity of development of an essentially humane and geographic climatology. This was the basic principle that guided the assignment. The work is based on two stages; the first one is theoretical-conceptual and the second one is practical-experimental. The former is supported by the debate of the concept of a nature justified by the urgency in approaching it to society into a motion which collaborates with an effective analysis of the environmental concerned issues faced nowadays. It is detachable that nature and society form a hybrid and it coincides with the thermodynamic subsystem-thermic comfort channel of the Urban Climate System-U.C.S.-proposed by Monteiro (1976). The latter refers to the analysis of the thermic field and to the environmental perception in Copacabana's neighborhood, studying field of this work, chosen because it introduces moderate intensity of the Urban Heat Island phenomenon- U.H.I.-cited by Brandão (1996). The regional and local climatic analysis and characterization, the site and the geographic position, the neighborhood morphology, the use of the soil; that is, the social-spacial dynamic in which nature is an important constituent-the hybrid dynamic -decisively contribute to the spacial arrangement of Copacabana's thermic field and Urban Heat Island phenomenon. The Urban Heat Island behavior is related to seasonality and to daily heating and cooling moments, included in the type of current weather, which was averred in the practical-experimental stage. High intensities occur in the winter at nine o'clock p.m. under the influence of the Tropical Atlantic Mass (TAM) due to the restrainment of the thermic energy occasioned by the high density of building constructions. Most of the neighborhood dwellers still do not perceive the phenomenon, principally its effects related to the discomfort caused by the heat and the human performance decline demonstrated, most of the times, by their uninterested and total lack of responsibility with ways and paces of living. However, the dwellers identify problems, suggest solutions and criticize responsible, but they do not include themselves as a responsible and they also do not realize themselves as a component of nature, part of the hybrid. Thus can be reflected how necessary self-regulative planned actions of the U.C.S could be debated without the effective involvement of society in their historical relationship determined within nature. Questions and relevant considerations will be raised to reflection. Wonder about the hybrid theorically is the first step of a long way, but about its effective practice?